DIFFERENCES IN THE VULNERABILITY OF MEDAKA FISH (Oryzias celebensisis) MALE AND FEMALE TO CLORPYRIPHOS INSETICIDE - Sulfitratullah Sulfitratullah; Khusnul Yaqin; Nita Rukminasari (AQUASAINS, 2022)
Chlorpyrifos is one of the most widely used organophosphate insecticides used to control pests on plants. The use of insecticides will produce residues in the soil and on plants and can be carried by rain flows to water bodies. This can pollute aquatic ecosystems and could negatively affected the growth of aquatic biota like Oryzias celebensis. This study aimed to determine the susceptibility of male and female medaka celebes (Oryzias celebensis) to chlorpyrifos insecticide. In this study, five fish medaka celebes were put in each jar in one jar for male medaka fish and female medaka fish with five replications. The parameters measured were survival rate, oxygen consumption rate between male and female of O. celebensis, temperature and pH. Statistically the survival rate of male and female medaka fish showed no statistically significant difference (P>0.05). Likewise, there was no difference between the oxygen consumption levels of male and female medaka fish before and after exposure to chlorpyrifos insecticide (P>0.05). This study concluded that there was no difference in susceptibility to chlorpyrifos insecticides between male and female medaka fish.